Fiqh Al-Ḣadîṡ Of Najs Removal - Mokhamad Sukron (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2021)
Everyday life offers new things, conditions and challenges that can affect the field of fiqh. As people face complex life, they demand further answer and explanation on how Islam deal with those issues. One which raise questions is the case of najs removal as it lies in central position of prayers. It becomes the foundation that determines whether the worship practice is lawful or not. This paper discusses the types of an-najs in al-fiqh al-Islamiyy and various methods of removing najs both classically and contemporary/modern, by providing accounts from the fiqh al-ḣadîṡ. By addressing this issue, this article aims at giving explanation on how fiqh on removal progresses following the context and is accommodating contemporary developments of Muslims’ lives.